Technologies for Libraries: A Bibliometric Analysis Based on Google Scholar - Karannagoda, Neluka Maduranga (South Asian University and LIS Academy, 2025)
Adopting technology in libraries has transformed their traditional roles, enabling them to function as vibrant centres of knowledge dissemination and innovation. Bibliometric analysis offers critical ...
Keywords: Library Technologies; Bibliometric Analysis; Citation Analysis; Google Scholar; Libraries